Islamic Religious Education, Parenting Styles and Their Influence on The Character of Generation Z - Mirza Mahbub Wijaya; Duwi Miyanto; Dwi Arni Siti Margiyanti (Sekretariat Badan Litbang dan Diklat Kementerian Agama RI, 2022)
This study focuses on the influence of Islamic religious education and parenting patterns on the characters of grade VII students at the Junior High School of Muhammadiyah 1, Semarang. This research was conducted because the author saw a decline in student characters. This research is a quantitative field with a Quantitative Positive approach. The step is to collect facts based on measurements of the symptoms that occurred in the previous respondent. This research was conducted at the Junior High School of Muhammadiyah 1 Semarang with three variables (X1, X2, and Y). Data sources were obtained through observation, documentation, and questionnaires with 120 respondents. Data analysis used in this reasearch was regression t and f tests (ANOVA). The analysis showed that the f (ANOVA) test was 1.399 with a significance value of 0.274. It means that there is a jointly significant contribution between the PAI variable and parenting patterns on students’ characters at the Junior High School of Muhammadiyah 1 Semarang. Thus, curriculum programs contain material oriented to human needs as servants of God to worship and social beings for society. It is necessary to improve the quality of teachers through coaching, starting from theory to the level of understanding and practice of action. Keywords: Islamic religious education, parenting, character